History of curricular changes of the bachelor in english teaching, Foreign Language Department, University of El Salvador, from 1972 to 2013 - Blanco Martínez, Igmar Mauricio
Learning a language is learning to communicate, since it is been living in a world of words and numbers because human beings always have had the need to communicate their ideas and thoughts among themselves. The ability to communicate has always been an important piece in human life because this has allowed human beings to transmit their new discoveries with the rest of the world; here is where emerged the need to acquire new language skills that can allow people to break the barriers of language. Since acquiring new language skills has been the necessity not only of one person but everybody, the idea arises as to find new ways to acquire these new abilities which lead to the creation of a new major tailored to supply this need. It was in this moment, when the University of El Salvador envisioned the importance of creating the Foreign Language Department to fulfill this need in the society. With the foundation of the Foreign Language Department, a Technical major was created named “Technical Major in Translation-Interpretation”, was served for a twelve-year period, from 1956 to 1968, being the year of 1972 when the foundation of a new major was established: the B.A. in English that began to be offered in 1973 to the students of that time. In this year 2013, the major has more than 40 years of existence since its foundation.